Determinan Kualitas Laporan Keuangan di Al Azhar Syifa Budi Solo - Ismunawan Ismunawan; Sriningrum Andayani (Jurnal Akuntansi dan Pajak, 2021)
This study aims to determine the effect of intellectual capital, internal control systems, and information technology on the quality of financial reports at Al Azhar Syifa Budi Solo, Surakarta City. The population of this study is the employees of Al Azhar Syifa Budi Solo, Surakarta City for users of financial statement information. And the sample is 100 employees. Data collection was obtained by distributing Likert scale questionnaires. The data were tested by: (1) Testing data quality, namely validity testing and reliability testing (2) classical assumption testing in the form of normality test, multicollinearity test, and heteroscedasticity test, (3) hypothesis in the form of descriptive statistical analysis, multiple linear regression analysis, F test, t test, and coefficient of determination test. The research revealed that intellectual capital had a significant effect on the quality of financial statements at Al Azhar Syifa Budi Solo, Surakarta City. The system of internal control has a significant effect on the quality of financial reports at Al Azhar Syifa Budi Solo, Surakarta City. And the use of information technology has no effect on the quality of financial reports at Al Azhar Syifa Budi Solo, Surakarta City.